RANCANGAN BANGUN SISTEM OTOMATIS PENGALIH SUMBER DAYA CADANGAN DC BERBASIS BATERAI PACK LITHIUM ION - Endang, Endang; Rahmat Hidayat (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2024)
The development of automatic control system technology, various practical and efficient tools have been created. The purpose of making these various tools is to make it easier to supply electronic electricity in everyday life. Continuous supply of electric power cannot be achieved if only using one power source, without a backup power source. On the other hand, if you use a backup power supply, you need a power supply switching system that works automatically and there is no delay or flashing. This research is related to the Design of Automatic System for Switching Backup Dc Resources Based on Lithium Ion Battery Packs, the purpose of this research is to design an automatic system that works to divert the source of equipment from the main source of PLN to a backup power source of Lithium Ion Battery Pack or vice versa so that the the availability of a power source does not affect the work of the tool. The results show that the designed system can work as expected with the limitation of the Lithium Ion Battery Pack battery with a capacity of 45Ah.